Knowledge sharing on implementing software process quality model evaluation: Focus group approach - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz (2014)
The Extended Software Process Assessment and Certification(SPAC) Model is a model that assesses and certifies the effectiveness and efficiency of software process, which focuses on the agile and secured based software development practices. The proposed model was evaluated using focus group approach.This approach is not often used in the software engineering field even though it has various benefits.Therefore, this paper shares the experiences on the implementation of the focus group for model evaluation to reveal its usefulness.The detailed discussion on the steps taken to implement the approach is discussed. Based on the experience, it is found that this approach is very time effective, can be conducted easily and can get more evaluation done at once